Pengembangan Media Pembelajaran Infografis Interaktif pada Materi Ekosistem pada Sekolah Dasar - Rabithah Zulsa Matondang; Jelita Jelita; Chery Julida Panjaitan (CAHAYA: Journal of Research on Science Education, 2026)
This study aims to develop interactive infographic-based learning media on ecosystem topics and to determine its feasibility and practicality. This study employs the ADDIE model for development, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 13 third-grade students, one teacher, and three expert validators. Data collection techniques included student and teacher response questionnaires as well as expert validation of the media, content, and language. Data analysis was conducted using quantitative and qualitative descriptive methods and was reinforced with Aiken’s V validity test. The results showed that the media received 100% content validation, 95% media validation, and 95% language validation, all categorized as highly feasible. Teacher responses scored 97.5% and student responses 90.57%, both categorized as “highly practical.” Thus, the developed instructional media is deemed suitable and practical for use in the classroom.